The power of certifications: how sustainability certifications impact the product preference in the brazilian juice market - Prell, Maximilian (2019)
Purpose – The purpose of this study was to investigate, in how far sustainability certifications impact the product preference in the Brazilian juice market. Design/methodology – Quantitative analysis was used applying conjoint analysis with different certifications and other product specifics embedded in a questionnaire design. Furthermore, cluster analysis was used to identify significantly different groups. Findings – In general, sustainability certifications increase the product preference in the Brazilian juice market. However, the effects between the clusters are different. The two most important segments are two, one is mainly dominated by price-sensitivity, the other is basing its choice mostly on the certification. Demographic differences as well as differentiation between the certifications are very limited. Research limitations – The study is investigating product preference, not actual buying behavior. Practical implications – The study provides a dual targeting strategy how to approach the two most important identified segments. Originality – Most prior studies are done in Europe or North America in the food market. Furthermore, comparisons between different certification groups are rarely conducted.